High-speed laser marking with diode arrays. (February 2022) - Bravo-Montero, Francesc; Castells-Rufas, David; Carrabina, Jordi
Highlights: Industrial printing applications demand higher throughput in-line digital laser marking. Single laser beam sequential processing limits marking speed to 8 m/s (de facto barrier). A laser beam matrix controlled by embedded computing overcomes marking speed barriers. Images of 50–200 dpi resolution, 6–50 mm width, speed up to 16 m/s can be printed. Even higher speeds can be achieved by investing in additional laser beams. Abstract: The creation of visible changes marked onto object surfaces by laser has become an effective way of coding industrial products. Industrial applications for printing solutions drive the demand for higher speed and higher throughput for in-line digital laser marking. Currently, most laser marking equipment is based on a single laser beam with the corresponding sequential processing that culminates in a performance bottleneck which limits printing production line speed to a de facto barrier of 8 m/s. In this paper, we present a system that overcomes this barrier by using a matrix of laser beams controlled by an embedded high-performance computing platform. The industrialized solutions presented in this paper can print images of 50 to 200 dpi resolution on printing substrates widths ranging from 6 mm to 50 mm, at product line speeds of up to 16 m/s. The analysis we have performed suggests that even higher speeds could be achieved by investing in additional laser beams.